1993
DOI: 10.1007/bf00198686
|View full text |Cite
|
Sign up to set email alerts
|

A blue-light photoreceptor mediates the fluence-rate-dependent expression of genes encoding the small subunit of ribulose 1,5-bisphosphate carboxylase/oxygenase in light-grown Phaseolus vulgaris primary leaves

Abstract: The level of transcripts of genes encoding the small subunit of ribulose 1,5-bisphosphate carboxylase/ oxygenase (rbcS genes) in the primary leaves of Phaseolus vulgaris L. increases substantially when plants grown in a low fluence rate of white light (15 ~tmol m 2 s-~; 400-700 nm) are transferred to a tenfold higher fluence rate of identical spectral quality. To investigate which photoreceptor acts as the fluence-rate detector, plants grown for 16 d in low white light were transferred to blue-enriched or red … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…Sawbridge et al (1994) and Lopez-Juez and Hughes (1995) showed that an increase in blue light enhanced transcription levels of the gene of rbcS, Rubisco, and cytochrome f proteins. The opening of stomata is promoted more strongly by blue than by red light.…”
Section: Short-term Exposure To Blue or Red Light At The Beginning Ormentioning
confidence: 99%
See 2 more Smart Citations
“…Sawbridge et al (1994) and Lopez-Juez and Hughes (1995) showed that an increase in blue light enhanced transcription levels of the gene of rbcS, Rubisco, and cytochrome f proteins. The opening of stomata is promoted more strongly by blue than by red light.…”
Section: Short-term Exposure To Blue or Red Light At The Beginning Ormentioning
confidence: 99%
“…In general, chlorophyll content increases while the ratio of photosystem II to photosystem I (PSII/PSI) decreases under increased R : FR conditions, indicating an involvement of the phytochrome system. However, the light intensity dependent increase in transcription level of the gene of small subunit of Rubisco (rbcS), another element of photosynthetic acclimation, was mediated specifically by blue light (Sawbridge et al, 1994). Lopez-Juez and Hughes (1995) showed that the chlorophyll a/b ratio, Rubisco, and cytochrome f proteins of pea seedlings (Pisum sativum L.) increased in response to an increase in blue light and suggested that a blue light photoreceptor controlled the light acclimation responses.…”
Section: Plant Responses To Light Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Other photomorphogenic systems are driven through UVA/blue light-and UVB-absorbing photoreceptors (10). In several species the increase in expression of rbcS upon illumination of dark-grown seedlings has been shown to be mediated by a phytochrome system (11)(12)(13)(14)(15)(16) (20). In none of these cases is it known whether signals cross over between postphotoperception signal transduction chains.…”
mentioning
confidence: 99%
“…Expression is also subject to temporal regulation during development (Nelson et al 1984;Greenland et al 1987;Wanner and Gruissem 1991). In most species, expression of the rbcS genes is stimulated by light mediated by phytochrome (reviewed by Tobin and Silverthorne 1985) or a blue-light photoreceptor Clugston et al 1991;Sawbridge et al 1994) depending on the stage of leaf development. In addition, expression is regulated by a range of other environmental and endogenous signals, including by metabolites such as sucrose and glucose (Sheen 1990;Krapp et al 1993).…”
Section: Introductionmentioning
confidence: 99%